Enhancement and confinement analysis of the electromagnetic fields inside hot spots - Perassi, Eduardo Marcelo (2009)
A novel and easy approach to implement is developed to analyze the degree of convergence, confinement, and enhancement (Γ) of calculated electromagnetic fields generated in plasmonic nanoparticles (NPs) of arbitrary shape. The approach is based on computing the variation of the volume trapped (VT) between a constant Γ surface around a metal NP and the nanoparticle surface boundary as a function of the enhancement itself. This method is a new and a more practically relevant approach to test the convergence than measures traditionally employed. For the test cases outlined here, the converged VT vs Γ curve could be fitted very accurately to a triple exponential expression which makes it convenient to determine the mean field enhancement within a trapped volume outside the NP, as well as the degree of localization and spreading of the hot spots (HSs) in 3D space. The technique introduced here should aid the understanding and a rational design of plasmonic devices based on metal NPs, where the near field plays a major role, such as in plasmon enhanced spectroscopies and plasmon imaging.